Analisis Harga, Kualitas Pelayanan dan Faktor Emosional terhadap Kepuasan Pelanggan di Laundry Super Wash - Tasya Hafifah; Hidayati Purnama Lubis (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to assess the factors that influence customer satisfaction, focusing on three primary variables: Price, Service Quality, and Emotional Aspects. The study employs an associative quantitative method, utilizing interviews and questionnaire distribution to customers of Laundry Super Wash in Medan. Multiple linear regression analysis is used to evaluate the extent to which each variable affects customer satisfaction. The findings indicate that Service Quality exerts the most dominant and significant influence, followed by Emotional Factors, whereas Price does not show a significant partial effect. The t-test results show that Price has a t-value of 3.413 > 1.663 but remains statistically insignificant; Service Quality has a t-value of 6.022 > 1.663, indicating significance; and Emotional Factors have a t-value of 3.167 > 1.663, also indicating significance. The F-test confirms that all three variables collectively have a significant impact on customer satisfaction. The coefficient of determination (R²) of 0.703 reveals that the regression model explains approximately 70.3% of the variance in Customer Satisfaction. Based on these findings, it is recommended that the company prioritize enhancing service quality and strengthening emotional connections with customers, while pricing can be considered a less critical factor in improving satisfaction.